PH-Responsive near-infrared fluorescent cyanine dyes for molecular imaging based on pH sensing. Issue 55 (26th June 2017) - Miki, Koji; Kojima, Kentaro; Oride, Kazuaki; Harada, Hiroshi; Morinibu, Akiyo; Ohe, Kouichi
Abstract : pH-Responsive near-infrared cyanine dyes were synthesized and applied as imaging probes of acidic intracellular compartments of living cells. Abstract : Indocyanine green (ICG) derivatives having nucleophilic substituents were synthesized as pH-responsive near-infrared dyes. pH-responsive dyes1-C with closed-ring structures smoothly internalized and converted to emissive open-ring structures1-O in response to relatively low pHs in acidic intracellular compartments of HeLa cells.